Quality of Life Assessment in Multiple Sclerosis: Different Perception between Patients and Neurologists - Ysrraelit, Maria C.; Fiol, Marcela P.; Gaitán, Maria I.; Correale, Jorge (Frontiers in Neurology, 2018)
Background: In recent years, neurologists are noticing that evaluation of Multiple Sclerosis (MS) patients based on combining relapses, disability progression and MRI activity may be insufficient to adequately assess suboptimal responses to available therapy. Inclusion of quality of life (QoL) parameters may contribute to breach this gap. Objective: To evaluate agreement levels between doctor and patient perception of QoL in MS. Methods: 700 MS patients and 300 neurologists were invited to participate in a cross-sectional study by answering an e-mail questionnaire. The survey collected information on demographical data and included the Short Form questionnaire (SF-36). After completing the questionnaire, patients were given a standard written description of each of the subdomains assessed by SF-36, and asked to identify which three were the most important determinants of their overall HRQoL. Results: A total of 135 neurologists and 380 MS patients responded the survey. Study population mean age was 42.1 ± 10.5 years, with 61% presenting relapsing-remitting MS. SF-36 results were physical function 68.4±30, physical role limitation 56.8±41.7, vitality 47.6±21.4, pain 71.2±26.1, social function 72.6±28.6, emotional role limitation 63.2±39.8, mental health 60±14.1 and general health 55.8±22. Doctors considered physical function (75%) and physical role limitation (70%) as the most important QoL determinants in MS, followed by emotional role limitation (52%). Patients however, assigned significantly different levels of importance to physical function (58%), and physical role limitation (46%) and considered vitality (52%) more important than their physicians (p<0.001). Important to note, the results of SF-36 questionnaire were highly correlated with the perception gap between patients and neurologists (r=0.89; p= 0.0004). Conclusions: Concerns on QoL in MS are different for patients and physicians. It is essential to enhance communication in order to better understand actual patient needs.